Advances of coupled water-heat-salt theory and test techniques for soils in cold and arid regions: A review - Zhang, Xudong; Shu, Changjian; Wu, Yajun; Ye, Peng; Du, Dewei (Geoderma, 2023)
•A discussion on the causes of soil salinization.•An overview of advances in water-salt transport research using temperature as a boundary.•A summary of experimental techniques in the field of water and salt transport research. Soil salinization is a global problem that severely restricts agriculture as well as the engineering and construction industry. Understanding water and salt transport laws is key to soil salinity improvement and prevention. This paper divides the development of the theory of water-salt migration into positive and negative temperature effects, taking temperature as the boundary. A review of the coupling of heat, salt, mechanics, and gas based on water-salt migration is included, and the generation of positive and negative temperature driving forces is analyzed along with the numerical models proposed in their development and the development of indoor experiments. In the end, a review of indoor tests and in situ soil salinity monitoring techniques is presented, and the shortcomings of soil salinity at this stage are summarized. Based on the above, an outlook on the future direction of soil salinization in a carbon–neutral environment is presented.